"Auch will ich Lernprozesse beobachten, um besser Mathematik zu verstehen.": Didaktische Rekonstruktion als mathematikdidaktischer Forschungsansatz zur Restrukturierung von Mathematik (mathematica didactica, 2005)
The article presents the research program Educational Reconstruction which has been developed in science education research. An example from elementary stochastics isused to explain how this program can be used for restructuring mathematics. The approach can also offer answers to the question of how to affiliate sustainable processes of conceptual change.